Surface coating method of sodium ion halide / sulfide solid electrolyte

By using magnetron sputtering to deposit the oxide solid electrolyte layer on the surface of sodium ion halide/sulfide solid electrolyte, the chemical reaction problem between sodium ion halide/sulfide solid electrolyte and liquid electrolyte is solved, and its application and cycle stability are improved in solid-liquid mixed semi-solid battery.

CN119890425APending Publication Date: 2025-04-25HUACAI (HEFEI) NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510029761.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Chemical reactions are prone to occur between sodium ion halide/sulfide solid electrolyte and liquid electrolyte, causing electrolyte to deteriorate and cannot be directly applied to semi-solid-state batteries that are mixed with solid and liquid.

Method used

The oxide solid electrolyte layer is deposited on the surface of the sodium ion halide/sulfide solid electrolyte by magnetron sputtering technology to form a dense coating to physically isolate the liquid electrolyte.

Benefits of technology

The chemical reaction between liquid electrolyte and sodium ion halide/sulfide solid electrolyte is effectively avoided, the interface stability of the positive and negative electrode sides is improved, and the application of halide/sulfide solid electrolyte in a semi-solid-state battery with solid-liquid mixed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890425A_ABST
    Figure CN119890425A_ABST
Patent Text Reader

Abstract

The invention discloses a surface coating method of a sodium ion halide / sulfide solid electrolyte. The surface coating method specifically comprises the following steps: preparing the sodium ion halide / sulfide solid electrolyte into an electrolyte film; and depositing oxide solid electrolyte layers on the surfaces of the two sides of the electrolyte film through magnetron sputtering. According to the surface coating method of the sodion halide / sulfide solid electrolyte provided by the invention, the oxide solid electrolyte layer is deposited on the surface of the sodion halide / sulfide solid electrolyte through a magnetron sputtering technology; therefore, the problem that the sodium ion halide / sulfide solid electrolyte and the liquid electrolyte are easily subjected to chemical reaction is solved, so that the sodium ion halide / sulfide solid electrolyte can be applied to a solid-liquid mixed sodium ion semi-solid battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion solid-state batteries, and in particular relates to a surface coating method for a sodium ion halide / sulfide solid electrolyte. Background Art

[0002] Sodium-ion batteries have similar working principles to lithium-ion batteries, and have significant advantages in terms of abundant sodium resources and low cost, and have attracted much attention in the market in recent years. However, the energy density of sodium-ion batteries is still lower than that of existing lithium-ion batteries, so it is of great significance to use solid electrolyte materials and combine high-specific-capacity positive and negative electrode materials to prepare sodium-ion solid-state batteries with high specific capacity and high safety.

[0003] Among several types of sodium ion solid electrolyte materials, halide / sulfide solid electrolytes have advantages such as high room temperature ionic conductivity and good processing performance, and have good development and application prospects. However, all-solid-state batteries based on halides / sulfides have problems such as low electrochemical window and serious interface side reactions between positive and negative electrodes. At the same time, solid electrolyte particles need to be mixed between the positive and negative electrodes, which reduces the energy density to a certain extent, and are still some distance away from commercialization.

[0004] If the solid electrolyte is mixed with the liquid electrolyte to prepare a solid-liquid mixed sodium ion semi-solid battery, it will have the high ionic conductivity and high interface wettability of the liquid electrolyte and the high safety of the solid electrolyte, which is the most promising solid electrolyte development route for mass production at this stage. However, due to the high reactivity of sodium ion halide / sulfide solid electrolytes, serious side reactions are likely to occur between them and organic solvents, causing the electrolyte to deteriorate and cannot be used with traditional carbonate electrolytes. Therefore, it is still difficult to directly apply sodium ion halide / sulfide solid electrolytes to solid-liquid mixed semi-solid batteries. Summary of the invention

[0005] Based on the above technical problems, the present invention provides a surface coating method for sodium ion halide / sulfide solid electrolytes. By using magnetron sputtering technology, an oxide solid electrolyte layer is deposited on the surface of the sodium ion halide / sulfide solid electrolyte, thereby solving the problem of easy chemical reaction between the sodium ion halide / sulfide solid electrolyte and the liquid electrolyte, so that it can be applied to solid-liquid mixed sodium ion semi-solid batteries.

[0006] The present invention provides a surface coating method for a sodium ion halide / sulfide solid electrolyte, comprising the following steps:

[0007] S1, preparing an electrolyte film from a sodium ion halide / sulfide solid electrolyte;

[0008] S2. Depositing an oxide solid electrolyte layer on both sides of the electrolyte film by magnetron sputtering.

[0009] In the present invention, the sodium ion halide / sulfide solid electrolyte film is effectively coated and modified by magnetron sputtering a dense coating of the sodium ion oxide solid electrolyte, which not only avoids direct contact between the sodium ion halide / sulfide solid electrolyte and the liquid electrolyte, so that the sodium ion halide / sulfide solid electrolyte can be applied to solid-liquid mixed semi-solid batteries, but also significantly improves the interface stability of the positive and negative electrode sides, thereby obtaining excellent cycle stability.

[0010] In the present invention, only by depositing the above-mentioned oxide solid electrolyte layer on the surface of the electrolyte film by magnetron sputtering can the cycle stability of the battery be effectively improved. If the oxide solid electrolyte layer is formed on the surface of the electrolyte film by other methods, for example, the sodium ion halide / sulfide solid electrolyte and the oxide solid electrolyte are directly composited into a film, or the surface of the electrolyte film is coated to form an oxide solid electrolyte layer, the former will passivate the activity of the halide / sulfide solid electrolyte due to the oxide solid electrolyte, and may even fail to inhibit short circuits. The latter is prone to excessive battery polarization, thereby reducing its electrochemical performance.

[0011] Preferably, the sodium ion halide / sulfide solid electrolyte is NaAlCl4, Na2ZrCl6, Na3ErCl6, Na3InCl6, Na 3-x Y 1-x Zr x Cl6、Na 1-x Zr x La 1-x Cl4、Na 0.5 AlCl 2.5 O 0.5 、Na3PS4、Na3SbS4、Na 11 Sn2PS 12 、Na 11 Sn2SbS 12 、Na 10 GeP2S 12 or Na4Sn 0.67 Si 0.33 At least one of S4.

[0012] Preferably, in step S1, the sodium ion halide / sulfide solid electrolyte is made into an electrolyte film by a sheet pressing method or a roller pressing method;

[0013] Preferably, the electrolyte film has a thickness of 10-1000 μm.

[0014] Preferably, in step S1, before the sodium ion halide / sulfide solid electrolyte is made into an electrolyte film by a sheeting method or a rolling method, the step further includes mixing the sodium ion halide / sulfide solid electrolyte and a binder;

[0015] Preferably, the added amount of the binder is 0.1-5 wt % of the sodium ion halide / sulfide solid electrolyte.

[0016] Preferably, the binder is polyethylene glycol modified polytetrafluoroethylene;

[0017] Preferably, the polyethylene glycol-modified polytetrafluoroethylene is obtained by coating polytetrafluoroethylene with dopamine and then condensing it with carboxylated polyethylene glycol methyl ether.

[0018] In the present invention, the polyethylene glycol modified polytetrafluoroethylene has abundant oxygen-containing and amino functional groups, which improves the bonding ability of polytetrafluoroethylene, ensures that the formed electrolyte film has a dense and smooth surface, and helps to form a dense modified layer of oxide solid electrolyte by subsequent magnetron sputtering deposition, further enhancing the physical isolation effect of sodium ion halide / sulfide solid electrolyte relative to liquid electrolyte; and can expand the Na + transmission channel to improve the cyclic stability of the obtained solid electrolyte.

[0019] Preferably, in step S2, the electrolyte film is used as a substrate and the oxide solid electrolyte is used as a target material, and magnetron sputtering is performed to deposit an oxide solid electrolyte layer on both sides of the electrolyte film;

[0020] Preferably, the oxide solid electrolyte is at least one of oxide β-Al2O3, sodium lanthanum zirconium oxide (NLZO), sodium phosphorus oxide nitrogen (NaPON), sodium aluminum germanium phosphate (NAGP), sodium aluminum titanium phosphate (NATP) and its derivatives or sodium lanthanum zirconium aluminum oxide (NLZAO);

[0021] Preferably, the oxide solid electrolyte layer has a thickness of 0.01-10 μm.

[0022] Preferably, the magnetron sputtering parameters include: the sputtering source is a radio frequency sputtering source, and the sputtering power density is 1-10 W / cm 2 , the sputtering pressure is 0.5-1.5 Pa, the sputtering distance is 2-20 cm, the sputtering atmosphere is argon and / or nitrogen, and the sputtering time is 10-180 min.

[0023] The present invention also provides a surface-coated sodium ion halide / sulfide solid electrolyte, which is prepared by the above method.

[0024] The present invention also provides a sodium ion semi-solid-state battery, comprising a positive electrode, a negative electrode and the above-mentioned surface-coated sodium ion halide / sulfide solid electrolyte.

[0025] Preferably, the sodium ion semi-solid battery further comprises a liquid electrolyte, wherein the liquid electrolyte comprises a carbonate, a sodium salt and an additive;

[0026] Preferably, the carbonate is at least one of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC) or ethyl methyl carbonate (EMC); the sodium salt is at least one of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium trifluoromethanesulfonate (NaOTf), sodium bistrifluoromethanesulfonimide (NaTFSI), sodium bisfluorosulfonimide (NaFSI), sodium bisoxalatoborate (NaBOB), sodium difluorooxalatoborate (NaODFB), sodium difluorophosphate (NaPO2F2) or sodium perchlorate (NaClO4); the additive is at least one of fluoroethylene carbonate, 1,3-propane sultone or vinyl sulfate;

[0027] Preferably, the additive is added in an amount not exceeding 5 wt%.

[0028] In the present invention, the selection of positive and negative electrodes is made according to actual needs. For example, the positive electrode active material can be selected from one of the transition metal oxide positive electrodes (sodium nickel manganese oxide, sodium iron manganese oxide, sodium nickel iron manganese oxide and similar positive electrodes derived therefrom, etc.), polyanion positive electrodes (sodium iron phosphate, sodium iron sulfate, sodium vanadium phosphate, sodium vanadium fluorophosphate, etc.), and Prussian blue / white analogs. The active material of the negative electrode can be selected from one of the metal sodium sheet, metal sodium alloy, hard carbon, soft carbon, and sodium titanate.

[0029] Compared with the prior art, the present invention has the following technical effects:

[0030] The present invention first prepares a sodium ion halide / sulfide solid electrolyte into an electrolyte film, and then deposits an oxide solid electrolyte layer on the surface of the electrolyte film by magnetron sputtering, thereby obtaining a surface-coated sodium ion halide / sulfide solid electrolyte. The present invention deposits a dense oxide solid electrolyte coating on the surface of the sodium ion halide / sulfide solid electrolyte film by a magnetron sputtering method, and forms physical isolation for the sodium ion halide / sulfide solid electrolyte by utilizing the dense oxide solid electrolyte coating, which effectively avoids the liquid electrolyte from penetrating into and contacting the sulfide / halide solid electrolyte, preventing the chemical reaction between the two from causing failure, and also avoids direct contact between the sulfide / halide solid electrolyte and the positive and negative electrodes, effectively improving the interface stability, and finally realizing the application of the halide / sulfide solid electrolyte in a solid-liquid mixed semi-solid battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a schematic diagram of the surface coating method of the sodium ion halide / sulfide solid electrolyte of the present invention. DETAILED DESCRIPTION

[0032] Hereinafter, the present invention will describe the technical solution in detail through specific embodiments, but it should be clearly stated that these embodiments are for illustration only and are not to be construed as limiting the scope of the present invention.

[0033] Example 1

[0034] This embodiment provides a surface coating method for a sodium ion halide solid electrolyte, comprising the following steps:

[0035] (1) rolling a sodium ion halide solid electrolyte powder (Na3YCl6) using a roller press at a rolling temperature of 60° C. to obtain an electrolyte film with a thickness of 60 μm;

[0036] (2) The above electrolyte film is used as a substrate, sodium lanthanum zirconium oxide (NLZO, Na7La3Zr2O 12 ) was used as the target material and the magnetron sputtering was carried out by radio frequency magnetron sputtering. The vacuum degree of the chamber was 1.0×10 -4 Pa, the working atmosphere is argon, the sputtering pressure is 1.0Pa, and the sputtering power density is 3W / cm 2 The sputtering distance was 5 cm, the sputtering time was 60 min, and an oxide solid electrolyte layer with a thickness of 0.45 μm was formed on both sides of the electrolyte film.

[0037] Example 2

[0038] This embodiment provides a surface coating method for a sodium ion sulfide solid electrolyte, comprising the following steps:

[0039] (1) Sodium ion sulfide solid electrolyte powder (Na 10 GeP2S 12 ) using a roller press to roll at a rolling temperature of 70° C. to obtain an electrolyte film with a thickness of 80 μm;

[0040] (2) The above electrolyte film was used as a substrate, and sodium phosphorus oxide nitrogen (Na2PO2N, NaPON) was used as a target material. The magnetron sputtering was performed by radio frequency magnetron sputtering. The vacuum degree of the chamber was 1.0×10 -4 Pa, the working atmosphere is nitrogen, the sputtering pressure is 0.8Pa, and the sputtering power density is 5W / cm 2 The sputtering distance was 3 cm, the sputtering time was 100 min, and an oxide solid electrolyte layer with a thickness of 0.56 μm was formed on both sides of the electrolyte film.

[0041] Example 3

[0042] This embodiment provides a surface coating method for a sodium ion halide / sulfide solid electrolyte, comprising the following steps:

[0043] (1) rolling a sodium ion halide / sulfide solid electrolyte powder (Na6PS5Cl) using a roller press at a rolling temperature of 80° C. to obtain an electrolyte film with a thickness of 40 μm;

[0044] (2) The above electrolyte film is used as a substrate, sodium germanium aluminum phosphate (Na 1.5 Al 0.5 Ge 1.5 (PO4)3, NAGP) was used as the target material and the magnetron sputtering was carried out by radio frequency magnetron sputtering. The vacuum degree of the chamber was 1.0×10 -4 Pa, the working atmosphere is argon / nitrogen mixed gas (volume ratio 2:1), the sputtering pressure is 0.6Pa, and the sputtering power density is 10W / cm 2 The sputtering distance was 8 cm, the sputtering time was 40 min, and an oxide solid electrolyte layer with a thickness of 0.35 μm was formed on both sides of the electrolyte film.

[0045] Example 4

[0046] This embodiment provides a surface coating method for a sodium ion halide solid electrolyte, comprising the following steps:

[0047] (1) adding sodium ion halide solid electrolyte powder (Na3YCl6) and polytetrafluoroethylene in a weight ratio of 99.6:0.4 to a planetary ball mill for uniform ball milling, with a ball-to-material ratio of 15:1, a ball milling speed of 500 rpm, and a ball milling time of 2 h. The obtained mixed powder is rolled using a roller press at a rolling temperature of 60°C to obtain an electrolyte film with a thickness of 60 μm;

[0048] (2) The above electrolyte film is used as a substrate, sodium lanthanum zirconium oxide (NLZO, Na7La3Zr2O 12 ) was used as the target material and the magnetron sputtering was carried out by radio frequency magnetron sputtering. The vacuum degree of the chamber was 1.0×10 -4 Pa, the working atmosphere is argon, the sputtering pressure is 1.0Pa, and the sputtering power density is 3W / cm 2 The sputtering distance was 5 cm, the sputtering time was 60 min, and an oxide solid electrolyte layer with a thickness of 0.45 μm was formed on both sides of the electrolyte film.

[0049] Example 5

[0050] This embodiment provides a surface coating method for a sodium ion halide solid electrolyte, comprising the following steps:

[0051] (1) adding sodium ion halide solid electrolyte powder (Na3YCl6) and polyethylene glycol modified polytetrafluoroethylene in a weight ratio of 99.6:0.4 to a planetary ball mill for uniform ball milling, with a ball-to-material ratio of 15:1, a ball milling speed of 500 rpm, and a ball milling time of 2 h. The obtained mixed powder is rolled by a roller press at a rolling temperature of 60°C to obtain an electrolyte film with a thickness of 60 μm;

[0052] Wherein, the polyethylene glycol-modified polytetrafluoroethylene is prepared by the following method:

[0053] Potassium permanganate (KMnO4) and nitric acid (HNO3) were added into water and dissolved completely to obtain a solution with a KMnO4 content of 6% and a HNO3 content of 18%. After adding polytetrafluoroethylene to immerse it, it was placed in a 60°C water bath and stirred for reaction for 3 hours. After filtering, pretreated polytetrafluoroethylene was obtained. Dopamine with a concentration of 1 mg / mL was added to the pretreated polytetrafluoroethylene and dispersed in a tris(hydroxymethyl)aminomethane buffer solution with a pH of 8.5. After high-speed stirring polymerization at room temperature for 24 hours, it was filtered, washed with water, and dried to obtain polydopamine-modified polytetrafluoroethylene. Polydopamine-modified polytetrafluoroethylene is added to a N,N-dimethylformamide (DMF) solution containing carboxylated polyethylene glycol monomethyl ether (mPEG-COOH), N-hydroxysuccinimide (NHS) and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDC), wherein the weight ratio of polydopamine-modified polytetrafluoroethylene, mPEG-COOH, NHS and EDC is 1:0.1:0.02:0.02, and the mixture is reacted at room temperature with high-speed stirring for 24 hours, filtered, washed and dried to obtain the polyethylene glycol-modified polytetrafluoroethylene;

[0054] The carboxylated polyethylene glycol monomethyl ether is prepared by the following method: polyethylene glycol monomethyl ether (mPEG, M n =1000), succinic anhydride (SA) and 4-dimethylaminopyridine (DMAP) were added to dichloromethane and stirred to dissolve completely, the weight ratio of polyethylene glycol monomethyl ether, SA and DMAP was 1:0.1:0.2, the temperature was raised to 60°C and stirred for reaction for 3h, dichloromethane was removed by rotary evaporation, the mixture was washed with ether and dried to obtain carboxylated polyethylene glycol monomethyl ether;

[0055] (2) The above electrolyte film is used as a substrate, sodium lanthanum zirconium oxide (NLZO, Na7La3Zr2O 12 ) was used as the target material and the magnetron sputtering was carried out by radio frequency magnetron sputtering. The vacuum degree of the chamber was 1.0×10 -4 Pa, the working atmosphere is argon, the sputtering pressure is 1.0Pa, and the sputtering power density is 3W / cm 2The sputtering distance was 5 cm, the sputtering time was 60 min, and an oxide solid electrolyte layer with a thickness of 0.45 μm was formed on both sides of the electrolyte film.

[0056] Comparative Example 1

[0057] This comparative example proposes a method for surface coating of a sodium ion halide solid electrolyte, which is referred to Example 1 except that step (2) is omitted.

[0058] Comparative Example 2

[0059] This comparative example proposes a surface coating method for a sodium ion sulfide solid electrolyte, which is referred to Example 2, except that step (2) is omitted.

[0060] Comparative Example 3

[0061] This comparative example proposes a surface coating method for a sodium ion halide / sulfide solid electrolyte, which is referred to Example 3, except that step (2) is omitted.

[0062] Comparative Example 4

[0063] This comparative example proposes a surface coating method for a sodium ion halide solid electrolyte, comprising the following steps:

[0064] Sodium ion halide solid electrolyte powder (Na3YCl6) and sodium lanthanum zirconium oxide (NLZO, Na7La3Zr2O 12 ) were added into a planetary ball mill at a weight ratio of 100:1.5 and milled evenly. The ball-to-material ratio was 15:1. The ball milling speed was 500 rpm. The ball milling time was 6 h. Roll pressing was then performed at a rolling temperature of 60°C to obtain an electrolyte film with a thickness of 60.9 μm.

[0065] Comparative Example 5

[0066] This comparative example proposes a surface coating method for a sodium ion halide solid electrolyte, comprising the following steps:

[0067] (1) rolling a sodium ion halide solid electrolyte powder (Na3YCl6) using a roller press at a rolling temperature of 60° C. to obtain an electrolyte film with a thickness of 60 μm;

[0068] (2) Sodium lanthanum zirconium oxide (NLZO) and acetonitrile are mixed in a weight ratio of 1:1 to obtain a slurry, and the slurry is evenly coated on both sides of the electrolyte membrane. After drying to remove the acetonitrile, an oxide solid electrolyte layer with a thickness of 0.45 μm is formed on both sides of the electrolyte membrane.

[0069] The surface-coated solid electrolyte obtained in Examples 1, 4, 5 and Comparative Examples 1, 4, 5 is directly placed on the sodium metal negative electrode and O3-NaNFMO (NaNi 0.33 Fe 0.33 Mn 0.33 O2) positive electrode, 1MNaPF6 / EC+DEC (1:1, mass ratio) liquid electrolyte is used to wet the positive and negative electrode interfaces and infiltrate the inside of the porous electrode. After packaging, the O3-NaNFMO||Na solid-liquid mixed sodium ion semi-solid battery is obtained.

[0070] The solid electrolyte obtained in the above-mentioned Example 2 and Comparative Example 2 is directly placed between the hard carbon negative electrode and the Na4V2(PO4)3 positive electrode, and a 1M NaPF6 / EC+EMC (1:1, mass ratio) liquid electrolyte is used to wet the positive and negative electrode interfaces and infiltrate the interior of the porous electrode. After packaging, a Na4V2(PO4)3||hard carbon solid-liquid mixed sodium ion semi-solid battery is obtained.

[0071] The solid electrolyte obtained in Example 3 and Comparative Example 3 was directly placed on the hard carbon negative electrode and P2-NaZNMTO (Na 0.64 Zn 0.05 Ni 0.29 Mn 0.56 Ti 0.11 O2) positive electrode, use 1M NaPF6 / EC+EMC+DEC+FEC (4.5:3:2:0.5, mass ratio) liquid electrolyte to wet the positive and negative electrode interface and infiltrate the inside of the porous electrode, and after packaging, the P2-NaZNMTO||hard carbon solid-liquid mixed sodium ion semi-solid battery is obtained.

[0072] The full battery cycle performance was tested on the Xinwei battery test system (25°C). For O3-NaNFMO||Na battery, the charge and discharge voltage range was 2-4V, and the charge and discharge current was 0.5C; for Na4V2(PO4)3||hard carbon battery, the charge and discharge voltage range was 2.5-3.65V, and the charge and discharge current was 0.5C; for P2-NaZNMTO||hard carbon battery, the charge and discharge voltage range was 2-4V, and the charge and discharge current was 0.5C. The test results are shown in Table 1 and Figure 1 .

[0073] Table 1 Comparison of the performance of the solid electrolytes obtained in the examples and comparative examples

[0074]

[0075] It can be seen from the results in Table 1 above that Examples 1-5 of the present invention can effectively improve the cycle stability of the sodium ion semi-solid battery; Comparative Examples 1-3 without surface coating modification and Comparative Example 4 of direct mixing cannot solve the problem that the halide / sulfide electrolyte and the liquid electrolyte in the sodium ion semi-solid battery are prone to chemical reactions; although the formation of the oxide solid electrolyte layer by coating can avoid the chemical reaction between the halide / sulfide electrolyte and the liquid electrolyte to a certain extent, it cannot improve the cycle stability of the sodium ion semi-solid battery.

[0076] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A surface coating method for a sodium ion halide / sulfide solid electrolyte, characterized in that: The steps include: S1, preparing an electrolyte film from a sodium ion halide / sulfide solid electrolyte; S2. Depositing an oxide solid electrolyte layer on both sides of the electrolyte film by magnetron sputtering.

2. The surface coating method of the sodium ion halide / sulfide solid electrolyte according to claim 1, characterized in that: The sodium ion halide / sulfide solid electrolyte is NaAlCl4, Na2ZrCl6, Na3ErCl6, Na3InCl6, Na 3- x Y 1-x Zr x Cl6、Na 1-x Zr x La 1-x Cl4、Na 0.5 AlCl 2.5 O 0.5 、Na3PS4、Na3SbS4、Na 11 Sn2PS 12 、Na 11 Sn2SbS 12 、Na 10 GeP2S 12 or Na4Sn 0.67 Si 0.33 At least one of S4.

3. The surface coating method of the sodium ion halide / sulfide solid electrolyte according to claim 1 or 2, characterized in that: In step S1, the sodium ion halide / sulfide solid electrolyte is made into an electrolyte film by a sheet pressing method or a roller pressing method; Preferably, the electrolyte film has a thickness of 10-1000 μm.

4. The surface coating method of the sodium ion halide / sulfide solid electrolyte according to claim 3, characterized in that: In step S1, before the sodium ion halide / sulfide solid electrolyte is made into an electrolyte film by a sheet pressing method or a roller pressing method, the sodium ion halide / sulfide solid electrolyte and a binder are mixed; Preferably, the added amount of the binder is 0.1-5 wt % of the sodium ion halide / sulfide solid electrolyte.

5. The surface coating method of sodium ion halide / sulfide solid electrolyte according to claim 4, characterized in that: The binder is polyethylene glycol modified polytetrafluoroethylene; Preferably, the polyethylene glycol-modified polytetrafluoroethylene is obtained by coating polytetrafluoroethylene with dopamine and then condensing it with carboxylated polyethylene glycol methyl ether.

6. The surface coating method of the sodium ion halide / sulfide solid electrolyte according to any one of claims 1 to 5, characterized in that: In step S2, the electrolyte film is used as a substrate and the oxide solid electrolyte is used as a target material, and magnetron sputtering is performed to deposit an oxide solid electrolyte layer on both sides of the electrolyte film; Preferably, the oxide solid electrolyte is at least one of oxide β-Al2O3, NLZO, NaPON, NAGP or NZSP; Preferably, the oxide solid electrolyte layer has a thickness of 0.01-10 μm.

7. The surface coating method of sodium ion halide / sulfide solid electrolyte according to claim 6, characterized in that: The magnetron sputtering parameters include: the sputtering source is a radio frequency sputtering source, and the sputtering power density is 1-10W / cm 2 , the sputtering pressure is 0.5-1.5 Pa, the sputtering distance is 2-20 cm, the sputtering atmosphere is argon and / or nitrogen, and the sputtering time is 10-180 min.

8. A surface-coated sodium ion halide / sulfide solid electrolyte, characterized in that: The invention is prepared by the method according to any one of claims 1 to 7.

9. A sodium ion semi-solid battery, characterized in that: It comprises a positive electrode, a negative electrode and the surface-coated sodium ion halide / sulfide solid electrolyte as claimed in claim 8.

10. The sodium ion semi-solid battery according to claim 9, characterized in that: The sodium ion semi-solid battery further comprises a liquid electrolyte, wherein the liquid electrolyte comprises a carbonate, a sodium salt and an additive; Preferably, the carbonate is at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate or ethyl methyl carbonate; the sodium salt is at least one of sodium hexafluorophosphate, sodium tetrafluoroborate, sodium trifluoromethanesulfonate, sodium bistrifluoromethanesulfonimide, sodium bisfluorosulfonimide, sodium bisoxalatoborate, sodium difluorooxalatoborate, sodium difluorophosphate or sodium perchlorate; the additive is at least one of fluoroethylene carbonate, 1,3-propane sultone or vinyl sulfate; Preferably, the additive is added in an amount not exceeding 5 wt%.